KEMAMPUAN SISWA DALAM MENGANALISIS MATERI SEJARAH DENGAN MENGGUNAKAN MODEL COOPERATIVE LEARNING TIPE THINK TALK WRITE (TTW) DI SMA NEGERI 1 PEKALONGAN - Eka Novita Sari; Elis Setiawati (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
Minimum completeness criteria (KKM) on the history lessons are 77. The purpose of the use of models of type Cooperative Learning Think Talk Write is to determine the effect of the use of models of type Cooperative Learning Think Talk Write the ability to analyze the historical material class XI IPS SMAN 1 Pekalongan second semester of academic year 2016/2017. Design in this research is Quasi Experiment with shapes pretest-posttest control group design, the sample was selected using random cluster sampling technique. In this activity, this study researchers used models of type Cooperative Learning Think Talk Write to encourage students to improve the ability to analyze. That the average yield of 78.24 experimental class learning and control class is 70.57 based on the average value obtained that the average value of 7.67 experimental class larger than the control class. Based on these calculations it can be concluded that the experimental class higher learning in the classroom compare control.